Karakteristik Determinan Kerusakan Fisik Arsip Rekam Medis Rawat Inap di Rumah Sakit Mitra Medika Medan - Manisha Manisha; Khoirotun Najihah; Yuniati Yuniati (Jurnal Kesehatan Amanah, 2024)
Medical records are essential documents that record healthcare service transactions. These files must be well-managed to maintain information accuracy and support service quality. The security and confidentiality of documents in the storage room are crucial, considering their value to the hospital. Proper management includes storage, security, and maintenance to prevent document damage. This study aims to identify factors influencing the physical deterioration of inpatient medical records at Mitra Medika Medan Hospital in 2024. The research method used is quantitative descriptive with observations and checklists on 98 samples determined through purposive sampling and calculations using Slovin's formula. The study was conducted from May 8, 2024, until completion, with data analysis using univariate tests. The study population consists of 5,271 medical record forms from January to December 2022. The results indicate that 76 documents were damaged, while 22 remained in good condition. Intrinsic factors include the lack of adhesive (92.9%), faded ink, and physical document damage. Extrinsic factors encompass dust, termites, direct sunlight exposure, and high humidity. Therefore, Mitra Medika Medan Hospital needs to enhance its document storage management to minimize determinant to record deterioration.